Combined Churg–Strauss syndrome and allergic bronchopulmonary aspergillosis – case report and review of the literature. (21st March 2012) - Ren, Shaohua
Abstract A rare case of combined Churg–Strauss syndrome (CSS) and allergic bronchopulmonary aspergillosis (ABPA) was presented. A 41‐year‐old woman was diagnosed with CSS based upon asthma, eosinophilia (23%), chest radiographic findings, paranasal sinusitis, peripheral neuropathy and positive p‐ anti‐neutrophil cytoplasmic antibodies (pANCA). The diagnosis of ABPA was established on the pathological findings of allegic mucin impaction and fungal hyphae on lung biopsy. It was further proved by positive serum IgE and IgG antibodies specific to afumigatus. The clinical investigation features were reviewed in the patients with combined CSS and ABPA. All patients had the time sequence of the development of CSS after ABPA uniformly, suggesting immunopathogenesis involving the emergence of CSS. The role of lung biopsy in the diagnosis of the condition was emphasized. Please cite this paper as: Ren S. Combined Churg–Strauss syndrome and allergic bronchopulmonary aspergillosis – case report and review of the literature. Clin Respir J 2013; 7: e6–e10.